Didymocarpus phuquocensis, a new species of Gesneriaceae from Phu Quoc Island, South-western Vietnam - Thi-Lien Tran; Ngoc-Sam Ly; Minh-Ngoc Tran; Xuan-Truong Nguyen; Ngoc-Giang Cao; Hong-Dung Pham (PhytoKeys, 2020)
A new species of Gesneriaceae, Didymocarpus phuquocensis, is described and illustrated from Phu Quoc National Park, Kien Giang Province, South-western Vietnam. It is most similar to D. pulcher, D. hookeri and D. punduanus in having 3-verticillate petiolate leaves, morphologically similar calyx, corolla, stamens, pistil and fruit, but differs from all in the glandular-pubescent stems, petioles and leaf blades, 1(–2)-flowered cymes, longer corolla and fruit and longer and densely glandular-puberulent ovary. Data on distribution, ecology, phenology and provisional conservation assessment of the new species are given along with an illustration and a colour plate.